PENGARUH SENAM OTAK TERHADAP PERKEMBANGAN BALITA DI TPA UNIK DAYCARE - Dewi Anggereni, Ni Made; Parwati, Ni Wayan Manik; Neza Dwiyanti, Ni Kadek; Diah Laksmi Dewi, Ni Komang (Jurnal Midwifery Update (MU), 2025)
A child's growth and development are inseparable from gross and fine motor skills. Optimal child development is achieved with appropriate stimulation. Children who receive focused and regular stimulation develop faster than those who receive little or no stimulation. Stimulation can be done through brain exercise. The purpose of this study was to determine the effect of brain exercises on toddler development at Unik Daycare. This study employed a quantitative study using a pre-experimental design in the form of a one-group pretest-posttest design. In this study, 34 respondents were recruited as a sample through a non-probability sampling in the form of total sampling. Data were collected using the KPSP questionnaire and the Brain Exercise SOP and analyzed using the Wilcoxon signed-rank test. Findings indicated that the pre-test results showed that most respondents (31 respondents or 91.2%) had questionable toddler development based on the KPSP. The post-test results after brain exercises showed that most respondents (32 respondents or 94.1%) had appropriate toddler development based on the KPSP. Analysis of the effect of brain exercises on toddler development yielded a p-value of 0.001 < 0.05. The study concludes that brain exercises have an effect on toddler development at Unik Daycare. This research can provide input for the community to apply brain exercise methods at home to optimize children's growth and development. Keywords: Toddler Development, Brain Exercises